Gerakan Sosial Anak Muda dalam Proses Demokrasi Elektoral 2024: Studi Gerakan Protes atas Politik Dinasti - Muliono, Muliono; Nasuhaidi, Nasuhaidi (Universitas Indo Global Mandiri, 2024)
This study aims to explore the youth social movements in the electoral democracy process of 2024. The social movement was triggered by the various situations that are related to the issue of political dynasty which is seen as producing a sense of injustice and a threat to democracy existence. This study uses a qualitative approach. The data is obtained and osberved from various social media reports on the protests against political dynasty issue. This study shows that the protest movement was carried out by more than 700 universities spread across various regions in Indonesia. The protest movement on the streets was dominated by the youth. This study formulates that the social movements carried out involving various framings and repertoires in building narratives for rejecting the political dynasty and demanding a systemic change. Actors in this social movements use social media as a tool for mass mobilization. However, the main challenge in this social movement comes from a strong cultural power system and a complex of democratic dynamics, which affect the results of the protest movement that carried out. Through these two challenges, the protest movement against political dynasty issue has not been so strong enough in accomodating, influencing and changing the political system will by the protesters. The contribution of this study is to expand the research issue related to new social movement that focuses on youth as movement’s actors and reveal the layered barrier or challenge of social movement in the context of Indonesia’s democracy.